2013
DOI: 10.2478/s11536-012-0119-4
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous adipose tissue measurements and better metabolic prediction

Abstract: AbstractThe aim of the study was to establish the importance of an additional measurement of subcutaneous adipose tissue thickness (SAT) on a predetermined position on the waistline, and its relation to waist measurements as an improvement of metabolic prediction in equally obese subjects. One hundred and forty two consecutive patients were enrolled in the study: stratified by weight as normal (body mass index — BMI 20–25 kg/m2), overweight (BMI 25–30 kg/m2) and obese (BMI >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
2
2
Order By: Relevance
“…An interest induced the data indicating that skinfolds from topographically neighboring areas were in a stronger correlation with each other, than did skin folds from distant topographical areas. Some authors have reported the importance of adipose tissue accumulation in the anterior abdominal wall [18]. In this investigation the sfAbdomen was the thickest, compared to the other studied skinfolds in patients with T2DM, but it was not detected a significant difference compared to the thickness of the corresponding skinfold in the controls.…”
Section: Discussioncontrasting
confidence: 62%
“…An interest induced the data indicating that skinfolds from topographically neighboring areas were in a stronger correlation with each other, than did skin folds from distant topographical areas. Some authors have reported the importance of adipose tissue accumulation in the anterior abdominal wall [18]. In this investigation the sfAbdomen was the thickest, compared to the other studied skinfolds in patients with T2DM, but it was not detected a significant difference compared to the thickness of the corresponding skinfold in the controls.…”
Section: Discussioncontrasting
confidence: 62%
“…Some authors have reported the importance of adipose tissue accumulation in the anterior abdominal wall. 17 In our investigation, the sfAbdomen was the thickest, compared to the other studied skinfolds in patients with T2DM, but it did not differ signifi cantly from the thickness of the corresponding skinfold in controls. Moreover, considerably greater thickness was measured in some skinfolds in the control group than in the corresponding skinfolds in patients with T2DM, as happened with sfTriceps, sfThigh and sfCalf.…”
Section: Discussioncontrasting
confidence: 48%
“…Fruit harvested while botanically mature gave quality seed in all tested variants, considering that those from fruit stored for 20 days after harvest had germination of 99%. By collecting eggplant in the second and third harvest, Ristić et al (2013) determined that seed obtained from fruit in the second harvest had lower germination than the seed from the third harvest. Storing seeds for three years increased germination in the first two, but germination decrease was noted in the third year.…”
Section: Seed Extraction Timementioning
confidence: 99%